Inhibition of deubiquitination by PR‐619 induces apoptosis and autophagy via ubi‐protein aggregation‐activated ER stress in oesophageal squamous cell carcinoma. (31st October 2020) - Wang, Longhao; Li, Miaomiao; Sha, Beibei; Hu, Xuanyu; Sun, Yaxin; Zhu, Mingda; Xu, Yan; Li, Pingping; Wang, Yating; Guo, Yanyan; Li, Jiangfeng; Shi, Jianxiang; et al.
Abstract: Objectives: Targeting the deubiquitinases (DUBs) has become a promising avenue for anti‐cancer drug development. However, the effect and mechanism of pan‐DUB inhibitor, PR‐619, on oesophageal squamous cell carcinoma (ESCC) cells remain to be investigated. Materials and Methods: The effect of PR‐619 on ESCC cell growth and cell cycle was evaluated by CCK‐8 and PI staining. Annexin V‐FITC/PI double staining was performed to detect apoptosis. LC3 immunofluorescence and acridine orange staining were applied to examine autophagy. Intercellular Ca 2+ concentration was monitored by Fluo‐3AM fluorescence. The accumulation of ubi‐proteins and the expression of the endoplasmic reticulum (ER) stress‐related protein and CaMKKβ‐AMPK signalling were determined by immunoblotting. Results: PR‐619 could inhibit ESCC cell growth and induce G2/M cell cycle arrest by downregulating cyclin B1 and upregulating p21. Meanwhile, PR‐619 led to the accumulation of ubiquitylated proteins, induced ER stress and triggered apoptosis by the ATF4‐Noxa axis. Moreover, the ER stress increased cytoplasmic Ca 2+ and then stimulated autophagy through Ca 2+ ‐CaMKKβ‐AMPK signalling pathway. Ubiquitin E1 inhibitor, PYR‐41, could reduce the accumulation of ubi‐proteins and alleviate ER stress, G2/M cell cycle arrest, apoptosis and autophagy in PR‐619‐treated ESCC cells. Furthermore, blocking autophagy by chloroquine or bafilomycin A1 enhanced the cell growth inhibition effect and apoptosis induced by PR‐619. Conclusions: Our findings reveal an unrecognized mechanism for the cytotoxic effects of general DUBs inhibitor (PR‐619) and imply that targeting DUBs may be a potential anti‐ESCC strategy. Abstract : PR‐619 could inhibit oesophageal squamous cell carcinoma cell growth and induce G2/M cell cycle arrest by downregulating the expression of cyclin B1 and upregulating the protein level of p21. Meanwhile, PR‐619 treatment led to the accumulation of ubiquitylated proteins, induced ER stress and triggered apoptosis by ATF4‐Noxa axis. Moreover, the ER stress increased cytoplasmic Ca 2+ and then stimulated autophagy through Ca 2+ ‐CaMKKβ‐AMPK signaling pathway.